Gut microbiota in liver diseases: initiation, development and therapy - Yu, Jian-Xiu; Wu, Jun; Chen, Xin; Zang, Su-gang; Li, Xue-bin; Wu, Li-Pei; Xuan, Shi-hai (Frontiers in Medicine, 2025)
The gut microbiota plays a pivotal role in the pathogenesis and progression of various liver diseases, including viral hepatitis, alcoholic fatty liver disease, metabolic dysfunction-associated steatotic liver disease, drug-induced hepatitis, liver cirrhosis, hepatocellular carcinoma, and other hepatic disorders. Research indicates that dysbiosis of the gut microbiota can disrupt the integrity of the intestinal barrier and interfere with the immune functions of the gut-liver axis, thereby mediating the progression of liver diseases. Analysis of microbial composition and metabolites in fecal samples can assess the diversity of gut microbiota and the abundance of specific microbial populations, providing auxiliary diagnostic information for liver diseases. Furthermore, interventions such as fecal microbiota transplantation, probiotics, prebiotics, bacteriophages, and necessary antibiotic treatments offer multiple approaches to modulate the gut microbiota, presenting promising new strategies for the prevention and treatment of liver diseases. This review summarizes the latest research advances on the role of gut microbiota in liver diseases, offering novel theoretical foundations and practical directions for the diagnosis and treatment of hepatic disorders.